2014
DOI: 10.1094/mpmi-10-13-0297-fi
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions of Two Amino Acids in the Nucleotide-Binding Site Domain of a Resistance Protein Enhance the Hypersensitive Response and Enlarge the PM3F Resistance Spectrum in Wheat

Abstract: Proteins with nucleotide-binding site (NBS) and leucine-rich repeat (LRR) domains are major components of the plant immune system. They usually mediate resistance against a subgroup of races of a specific pathogen. For the allelic series of the wheat powdery mildew resistance gene Pm3, alleles with a broad and a narrow resistance spectrum have been described. Here, we show that a broad Pm3 spectrum range correlates with a fast and intense hypersensitive response (HR) in a Nicotiana transient-expression system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 65 publications
3
76
0
Order By: Relevance
“…Consistent with previous studies using autoactive PM3 proteins (Stirnweis et al, 2014a(Stirnweis et al, , 2014b, transient expression of AvrPm3 a2/f2 with Pm3a, Pm3f, or Pm3f L456P/Y458H in N. benthamiana led to cell death. In wheat, transient expression of AvrPm3 a2/f2 with Pm3a led to a significant reduction in the number of cells accumulating the GUS reporter, as did the autoactive Pm3a HR construct, likely because of an activation of Pm3a by AvrPm3 a2/f2 resulting in cell death.…”
Section: Identification Of Avrpm3 A2/f2supporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with previous studies using autoactive PM3 proteins (Stirnweis et al, 2014a(Stirnweis et al, , 2014b, transient expression of AvrPm3 a2/f2 with Pm3a, Pm3f, or Pm3f L456P/Y458H in N. benthamiana led to cell death. In wheat, transient expression of AvrPm3 a2/f2 with Pm3a led to a significant reduction in the number of cells accumulating the GUS reporter, as did the autoactive Pm3a HR construct, likely because of an activation of Pm3a by AvrPm3 a2/f2 resulting in cell death.…”
Section: Identification Of Avrpm3 A2/f2supporting
confidence: 91%
“…Brunner et al (2010) previously demonstrated that the two alleles Pm3f and Pm3a have characteristic resistance spectra: Based on the observation that all the isolates recognized by Pm3f were also recognized by Pm3a, but not vice versa, they concluded that Pm3a is a stronger form of Pm3f. Later, Stirnweis et al (2014a) showed that a substitution of only two amino acids in the NBS domain of PM3F (PM3F L456P/Y458H ) was sufficient to broaden Pm3f-mediated resistance to potentially confer the same race specificity as Pm3a, thus substantiating the hypothesis that Pm3a is a stronger version of Pm3f. Therefore, to test for interaction with the resistance gene, Pu_3 and Pu_7 were cloned from the avirulent parent 96224 (Pu_3 avr and Pu_7 avr ) and the virulent parent 94202 (Pu_7 vir ).…”
Section: Identification and Functional Validation Of Avrpm3 A2/f2mentioning
confidence: 92%
See 3 more Smart Citations